FRAMING FERIYANI LIM DALAM KASUS FOTO MESRA ABRAHAM SAMAD DAN FERIYANI LIM DI PORTAL BERITA ONLINE TRIBUNNEWS.COM - Maheswari, I Gst. Ag. Dyah; Amanda Gelgel, Ni Made Ras; Pascarani, Ni NyomanDewi (E-Jurnal Medium, 2017)
ABSTRACT Media has full authority in determining the priority issues and protrusion the aspect of news. Women looked dominant as an object highlighted in the news. Content imbalance between men and women makes framing news about women more attractive to investigate. Based on the background of these issues, this study aims to find how the framing of Feriyani Lim in the case of Abraham Samad and Feriyani Lim's intimate photo in Tribunnews.com. Research data: Tribunnews.com news period February 3, 2015 - 11 March, 2015. This study uses a constructivism with approach of qualitative research. Analysis research method of framing models by William A Gamson used for identify the framing device and reasoning device. Framing device consist of : (1) metaphors, (2) depiction, (3) catchphrases, (4) Examplaar, (5) Visual Image. Reasoning devices consist of: (1) roots, (2) appeals to principle, (3) concequences. The results showed depictions of Ferniyani Lim tend to show Feriyani Lim's image as a woman who is considered sexy, prostitute, has Chinese ethnic and has a luxurious lifestyle. Keywords: framing, intimate photos, women